Thermal Investigation on Lithium-Ion Battery Using Liquid Cooling Method - Stefan Mardikus; Petrus Setyo Prabowo; Bernadeta Wuri Harini; Budi Sugiharto; F. A. Rusdi Sambada; Achilleus Hermawan Astyanto; I. M. W. Ekaputra (International Journal of Applied Sciences and Smart Technologies, 2026)
An electric battery is an energy storage device that has a high energy density, a long lifetime and has a high rate of charging and discharging the battery. The performance of the Lithium-Ion battery greatly affects the temperature of charging and discharging, so a cooling method is needed that is able to maintain the working temperature of the battery at (250C – 500C) conditions. In this study, the Computational Fluid Dynamics method was used to investigate the effect of Depth of Discharge (DOD) on the cooling performance of BTMS (Battery Thermal Management System) Liquid Cooling using ethylene-glycol as the working fluid to be flowed on the curved cooling tube. The results of this study indicated that the maximum temperature and temperature difference of the battery module decreased as the mass flow rate of the cooling fluid increased, the lowest temperature value occured at the mass flow rate of 18×10-4kg·s-1 with a temperature value of 303.6 K. The maximum temperature of the battery module fluctuated as the DOD value increased.